Distinguish Sea Turtle and Fish Using Sound Technique in Designing Acoustic Deterrent Device - Azrul Mahfurdz; Sunardi Sunardi; H. Ahmad; Syed Abdullah; Nazuki Nazuki (Universitas Ahmad Dahlan, 2015)
Acoustic is a common method for underwater object classification and to observe fish schools or other marine animals in their environment, but it was never applied on sea turtle. Knowledge about turtle detection using sound is very limited and there are no target strength (TS) recorded before. In this study, an echo voltage reference methodincorporating standard target was used to measure ex situ target strength of two Green Turtle (Chelonian mydas) and three species of fish (Indian scad, Indian Mackerel and Bigeyescad). The echo signal of animals has been observed from echosounder output and every envelope of the echo was digitized at a sampling rate 1MHz using high speed analog to digital converter (USB‑1208HS). The finding shows a significant difference between fish and turtles aged 18 years old. The result also demonstrates that TS increase as age of turtle increase. This result is considered important in designing an acoustic deterrent device. The result reveals that size, surface, and animal body part influence in determining target strength value.